IDENTIFICATION OF ALTERATION AREAS BASED ON SENTINEL-2 SATELLITE IMAGERY AND VEGETATION RESPONSE FOR GEOTHERMAL EXPLORATION IN VOLCANIC FIELDS - Eka Rahmidiani, Wina
Geothermal fields are generally located in remote areas with dense vegetation cover, making early-stage exploration time-consuming. Remote sensing becomes a viable solution to support preliminary surveys as it can identify areas with high vegetation cover by analyzing the vegetation response. Thus, it is expected that early-stage exploration can be conducted more effectively and efficiently. Geothermal manifestations, such as fluids and gases, can cause vegetation stress that impacts plant health. Evidence of geothermal manifestations can be seen in surface features such as hot springs, steam vents, and fumaroles, which can be detected using remote sensing methods. This study aims to detect alteration areas using Sentinel-2B imagery, identify vegetation responses in alteration and non-alteration areas, and analyses the effectiveness of the REVI vegetation index from Sentinel-2B imagery for geothermal exploration at Mount Tangkuban Parahu and Kamojang (West Java) and Mount Ijen (East Java). The data used includes Sentinel-2B imagery and chlorophyll measurements of ferns. Methods used include band ratios and vegetation indices to identify alteration areas and vegetation stress. Plants experiencing vegetation stress due to growing in contaminated soil can serve as indirect indicators of geothermal systems. The results show that band ratios and vegetation indices align with chlorophyll measurements in ferns in the field. Based on Sentinel-2B imagery, alteration areas are identified with RGB composite using bands 4/2, 11/12, and 11/8A as magenta. Enhancing the colour contrast of the imagery shows sharper results and makes alterations more visible. This is further verified by the identification of the Red Edge Vegetation Index (REVI), which shows that the identified alteration area has a low REVI value of 0,3. This indicates that plants in these areas grow increasingly sparse in response to growing in conditions that are not ideal for plant growth, resulting in suboptimal growth. As a defense mechanism, plants exhibit different appearances, becoming drier, stunted, or in extreme conditions, causing plant death. Measurements of chlorophyll values in endemic plants confirm that vegetation in the alteration areas is under stress, with chlorophyll values below 10 SPAD.